OARSI Clinical Trials Recommendations: Design and conduct of clinical trials for hand osteoarthritis. Issue 5 (May 2015) - Kloppenburg, M.; Maheu, E.; Kraus, V.B.; Cicuttini, F.; Doherty, M.; Dreiser, R.-L.; Henrotin, Y.; Jiang, G.-L.; Mandl, L.; Martel-Pelletier, J.; Nelson, A.E.; Neogi, T.; et al.
Summary: Hand osteoarthritis (OA) is a very frequent disease, but yet understudied. However, a lot of works have been published in the past 10 years, and much has been done to better understand its clinical course and structural progression. Despite this new knowledge, few therapeutic trials have been conducted in hand OA. The last OARSI recommendations for the conduct of clinical trials in hand OA dates back to 2006. The present recommendations aimed at updating previous recommendations, by incorporating new data. The purpose of this expert opinion, consensus driven exercise is to provide evidence-based guidance on the design, execution and analysis of clinical trials in hand OA, where published evidence is available, supplemented by expert opinion, where evidence is lacking, to perform clinical trials in hand OA, both for symptom and for structure-modification. They indicate core outcome measurement sets for studies in hand OA, and list the methods and instruments that should be used to measure symptoms or structure. For both symptom- and structure-modification, at least pain, physical function, patient global assessment, HR-QoL, joint activity and hand strength should be assessed. In addition, for structure-modification trials, structural progression should be measured by radiographic changes. We also provide a research agenda listing many unsolved issues that seem to most urgently need to be addressed from the perspective of performing "good" clinical trials in hand OA. These updated OARSI recommendations should allow for better standardizing the conduct of clinical trials in hand OA in the next future.